The differences in postural stability between cross-country and Alpine skiers with intellectual disabilities - Gimunová, Marta; Skotáková, Alena; Grün, Vojtěch; Jenčíková, Kateřina; Daněk, Leoš; Hlinský, Tomáš; Svobodová, Lenka; Kalichová, Miriam; Válková, Hana (Acta of bioengineering and biomechanics, 2020)
PURPOSE: The purpose of this study was to analyse differences in postural stability between athletes with ID competing in Alpine and Cross country (XC) skiing to assess the effect of special sports training on postural stability in persons with ID. METHODS: Athletes with ID were divided into four groups by their discipline: Alpine skiers (n = 9), XC skiers 2.5 to 10 km (n = 10), XC skiers 500 to 1000 m (n = 18) and XC skiers 50 and 100 m (n = 10). All participants were asked to stand barefooted on the Zebris FDM platform (Medical GmbH, Germany) with their eyes open and closed. To compare differences between groups one-way ANOVA with Tukey HSD test was used. To compare the difference between the eyes open and closed, t-test was used. RESULTS: Statistical analysis showed no significant differences between Alpine and XC skiers in analysed variables. The analysis of COP velocity showed superior postural stability in XC skiers 2.5 to 10 km compared to XC skiers 500 and 1000 m. In XC skiers 500 and 1000 m, XC skiers 2.5 to 10 km and Alpine skiers a significant increase in COP velocity was observed when having the eyes closed. In XC skiers 50 and 100 m, no statistically significant differences between the eyes open and closed conditions were observed. CONCLUSIONS: Despite different sports training, no difference between Alpine and XC skiers in postural stability was observed. When comparing XC skiers, better postural stability was observed in skiers running longer distances, suggesting that this sports training enhances balance skills needed in everyday life.